Perspektif Hukum Ekonomi Syariah Dalam Akad Murabahah Pada Produk Cicil Emas Di BPRS PNM Mentari Garut - Gaussian, Gini; Elisa, Eceu (STAI Al Musaddadiyah Garut, 2024)
BPRS PNM Mentari Garut has issued a gold installment product, namely a consumer financing product of an investment nature with the aim of attracting customer iterest, and using a murabahah contract. Buying and selling gold ownership without cash (in installments) there are different views among scholars (Islamic scholars and contemporary scholars) some allow it and some do not allow it. It is stated in the research title with the formulation of the problem, how is the Murabahah Contract mechanism and what is the Shariah Economic Law Perspective on Gold Installment Products at BPRS PNM Mentari Garut. The purpose of this study is to determine the mechanism of the murabahah contract and to determine the perspective of Islamic Economic Law on gold instalment products at BPRS PNM Mentari Garut. This research is a field research that uses qualitative methods and descriptive analytical research nature, supported by literature studies. Based on research results, the use of the murabahah contract according to scholars is valid and permitted, because the use of the murabahah contract is analogous to the law of the contract that establishes it.This will provide an opportunity to create a murabahah contract for gold installment products at BPRS PNM Mentari Garut. This gold installment financing does not have any harm, difficulties and constraints for the bank or its customers. In this transaction it is safer and reduces the potential risk of loss between both parties. Keywords: Murabahah; Golden Installment; Shari'ah Economic Law;